(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2024)
The research examines the bibliography required by the student of the subject Public Administration I of the Dean of Economics and Business Sciences (DCEE) of the Universidad Centroccidental Lisandro Alvarado (UCLA), in response to the new emerging situations in Venezuela, regarding the restructuring of the Venezuelan State with a constitutional foundation and legal, specifically in the topic of “Planning”, and the terminal objective of thematic Unit IV of the program. First, general considerations on the topic “Planning” were addressed, as part of the Public Administration I program, and the nature of the knowledge inherent to it as the thematic unit of said subject was reflected on. Then, the bibliography is studied, the concept is delimited based on a brief reflection on the content and meaning of this category in the contemporary debate, the selection of material is analyzed and what the bibliography is by unit and/or is briefly addressed or general and the recommended or complementary bibliography and reflects on the updating of the bibliography and information society, this in accordance with the objectives proposed in the research. Taking into account the nature of the research, the objectives set and the qualitative approach, it was based on the progressive construction of knowledge as it emerges in reality. The method used was hermeneutic. The sample was intentional or based on criteria. The qualitative analysis of the documents was carried out based on a theoretical framework and prior knowledge of the context in which this work was prepared.